Reflective LCD without Flicker for Reduced Eye Strain. Issue 1 (June 2014) - Fukai, Shuji; Niikura, Yasuhiro; Kobayashi, Manabu; Ikenaga, Makoto; Hatsumi, Ryo; Nishi, Takeshi; Ishitani, Tetsuji; Hirakata, Yoshiharu; Koyama, Jun; Yamazaki, Shunpei; Sato, Rai; Cho, Takayuki
Abstract We fabricated a 6.05‐inch reflective liquid crystal display (LCD) using a CAAC‐OS for a driving transistor. We achieved low frequency driving at 1/60 fps or lower and flicker reduction. With our LCD, eye strain can be reduced more than with an electrophoretic display.